Odziv kambija navadne smreke (Picea abies) na ogrevanje in hlajenje debla - Gričar, Jožica (Zbornik gozdarstva in lesarstva, 2004)
The effect of experimental heating and cooling in a part of the stem of Norwayspruce (Picea abies) on cambial activity and cell differentiation was studied. Experiments were performed for 30 days; heating from 29 March 2004 until 3 May 2004 and cooling from 14 June, 2004 until 20 July 2004. Samples ofphloem, cambium and xylem were taken from trees every 10 days, transverse sections of tissue were prepared and observed under light microscope. After 10days, localized heating reactivated cambial cell division on the phloem sideand after 20 days on the xylem side as well. After 30 days up to 15 early wood cells were formed in the heat-treated sample. Regular cambial activity inthe control tree only started after 30 days. Cambial response to the coolingof the stem was less conspicuous. No anatomical differences were detected between the control and cool-treated samples after 10 and 20 days. After 30 days, late wood already started to form in the cool-treated sample and only transition early-late wood in the control tree. Our experiments demonstrated that it is possible to influence xylo- and phloemogenesis in Norway spruce by experimental heating and cooling of the stem.
Keywords: celična diferenciacija; kambij; navadna smreka; Picea abies; svetlobna mikroskopija; vpliv temperature